Centenary of the Societe de Statistique de Paris - Lyon, Stanley (Statistical and Social Inquiry Society of Ireland, 1961)
The President of the Societe de Statistique de Paris sent the following invitation to the President of the Statistical and Social Inquiry Society of Ireland requesting him, or a deputy on his behalf, to attend at the Centenary Celebrations of the foundation of the Societe de Statistique de Paris.
One Hundredth and Fourteenth Session ? 1960/61
Keywords: Societe de Statistique de Paris; Statistical and Social Inquiry Society of Ireland; 314.15